Changes in serum concentration of perioperative inflammatory cytokines following the timing of surgery among mild–moderate traumatic brain injury patients and factors associated - Hervé Monka Lekuya; Hervé Monka Lekuya; Stephen Cose; Marjorie Nakibuule; Gift Ahimbisibwe; Anthony Fuller; Larrey Kasereka Kamabu; Emmanuel Biryabarema; Geoffrey Olweny; David Patrick Kateete; Anthony Kirabira; Fredrick Makumbi; et al. (Frontiers in Neurology)
BackgroundThe safe timing window for surgery during the acute phase of inflammation due to traumatic brain injury (TBI) has not been studied extensively. We aimed to elucidate the relationship between the timing of surgery and changes in perioperative serum levels of inflammatory cytokines and factors associated to optimize TBI management in low-middle-income countries.MethodsA prospective cohort study was conducted among TBI Patients with depressed skull fractures with a GCS > 8 operated at different timing from injury and followed up peri-operatively. We collected the clinical-radiological data, as well as pre-and postoperative venous samples from participants; we then did Luminex Assay to quantify the serum levels of pro/anti-inflammatory cytokines using the kits of 96-well human cytokine “27-Plex-Assay (#M500KCAF0Y®).” We performed the analysis with STATA version 17 and R_studio applying both descriptive and inferential methods.ResultsWe enrolled 82 TBI patients with a median (IQR) age of 25.5 (20–34) years, and the majority were male (85.4%). There were 48.8% victims of assaults, and 73.2% had a post-resuscitation admission GCS of 14–15. There were 38 (46.3%) who were operated within 48 h of injury versus 44 (53.7%) after 48 h. Serum levels of TNF-α were significantly higher after surgeries done >48 h compared to those done ≤48 h (p = 0.0327); whereas, the difference in post-operative mean serum levels of IL-10 was significantly increased in patients who developed later SSI compared to those who did not (11.56 versus −0.58 pg./mL, p = 0.0489). In multivariate analysis, the history of post-traumatic seizure (PTS) was associated with a postoperative increase in TNF-α (p = 0.01), the hemoglobin of 10–12 with a postoperative decrease of IL-4 (p = 0.05); the presence of focal neurological deficit was associated with a significant postoperative increased of TNF-α, IL-6, and IL-4 (p = 0.05). The presence of extra-axial hemorrhage was associated with a postoperative increase of IL-10 (p = 0.05).ConclusionDelayed surgical intervention beyond 48 h post-injury in mild–moderate TBI patients results in a significantly increased postoperative inflammatory response, as evidenced by elevated serum levels of TNF-α and IL-6. Neurological deficits, PTS, reduced hemoglobin rate, and extra-axial intracranial hemorrhage are factors associated with this heightened response.